Implementasi Metode Al-Wasail Dalam Meningkatkan Qiro’atul Kutub Di Madrasah Ibtida’iyah Salafiyah Syafi’iyah Al Ihsan Jrangoan Omben Sampang - Hasyim Asy’ari, Moh.; Azmi fatoni, Moh.; Lutfiyati, Lutfiyati; Bukhori, Bukhori (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
The focus of this research is to find out how the implementation of qiroatul qutub in madrasah ibtida'iyah salafiyah syafi'iyah Al ihsan jrangoan. The method used in this research is a quantitative method, with data collection using interview techniques. From the results of this study it was concluded that at Madrasah Ibtida’iyah salafiyah syafi'iyah Al ihsan jrangoan omben sampang there is the implementation of qiroatul qutub with the Al-Wasail method, namely the yellow book fast learning method with a time allocation of 90 minutes in the morning at 07:35, in the afternoon at 16:30 and in the evening at 20 :00 special time' student competency standard or students can memorize Al-Wasail material read and practice it, but the method is still specifically for boys only while the indicators in the Al-Wasail method students or students can explain binak, division of fi'il and fail, various kinds of isim, fi 'il and letters, various kinds of i'rob, mabni and can read examples of material in Al-Wasail. The sources and learning tools are a package of the Al-Wasail book, a dictionary, a memorization deposit book, the book of fathul qorib written by Abu Syuja